Development of Septic Tank Monitoring System through Sensor Technology and Augmented Reality - Winata, Stephen; Haryono, Haryono (JINAV: Journal of Information and Visualization, 2023)
Septic tank is a dumping place for human waste. However, the presence of septic tanks can also cause many diseases and dangers to the environment. Leaking or overflowing septic tanks can threaten the surrounding environment. This research aims to design and develop a system that can monitor the volume and gas levels in septic tanks to prevent hazards caused by uncontrolled septic tanks. The researcher utilized MQ-4 sensor and JSN-SR04T distance sensor to detect volume and gas in septic tanks. In order to retrieve data from the sensor, a microcontroller is required that uses ESP 32 as a liaison between the sensor and Blynk. Blynk is used as a connecting application between augmented reality and microcontrollers. Data sent from Blynk was then retrieved through the Blynk API and can be displayed on augmented reality using Unity's Vuforia SDK. The researcher employed the prototype method in this study to design the application prototype. This application can run smoothly and provide accurate data on the volume and gas in the septic tank. Thus, this monitoring system can help to prevent environmental and human health damage caused by uncontrolled septic tanks.